KEY FACTORS INFLUENCING LEARNERS’ ORAL FLUENCY IN ENGLISH SPEAKING CLASSES: A CASE AT A PUBLIC UNIVERSITY IN VIET NAM - Ngoc, Dinh Thi Bich; Dung, Tran Thi (VNU Journal of Foreign Studies, 2020)
In the field of English language learning, speaking is regarded as one of the most important skills to be developed and enhanced continually as means of effective communication. In most English classes at universities, many students find it difficult to express themselves in spoken English. So this research aims to investigate prominent factors affecting fluency of second-year students in speaking skill. The study uses mixed research methods with two data collection instruments namely survey questionnaire and semi-structured interview. The participants joining the survey questionnaire include 98 English non-majored students who were taking the English speaking course in their second semester at a university. The semi-structured interviews were conducted with 15 teachers and 15 students. The findings reveal that the group of affective factors is the prominent one, and then followed by automation, error correction and performance factors influencing their oral fluency. Therefore, some useful recommendations focusing on interactive strategies to minimize learners’ difficulties in oral fluency as well as develop their fluency in English speaking performance in this study could be taken into account for EFL teachers in English speaking classes.